IMPROVEMENT OF SOY SAUCE INOCULUM QUALITY USING A MIXED CULTURE OF ASPERGILLUS ORYZAE TG1 AND MICROCOCCUS LUTEUS - Pudjiraharti, S. (Teknologi Indonesia, 2009)
The aim of this research is to improve the quality of soy sauce inoculum by increasing the activity of enzymes containing in inoculum which is needed for the degradation of soybean nutrition compounds. A mixed culture of Aspergillus oryzae TG1 and Micrococcus luteus with various ratio of colony number were used for inoculum preparation.The ratio of A.oryzae TG1 to M. luteus were 1:0, 1:0.25, 1: 0.50, 1:0.66, and 1:1. Incubation was done at 30 oC for four days. Inoculum with the highest enzyme activity was applied for koji preparation. The result of experiment showed that a mixed culture with ratio 1:0.25 indicated a positive effect on inoculum quality by resulting the highest activity of all enzymes tested. The Activity of ?-amylase enzym was 2055.1 Units/g, protease was 17.1 Units/g, and ?-glucosidase was 18.3 Units/g. They were observed at four days incubation. Total plate count analysis of this inoculums resulted 1.14 x 1011 cfu of A. oryzae and 2.05 x 109 cfu of M. luteus per g inoculum which were higher than that of starter. Application of the inoculums with ratio of 1:0.25 for koji preparation showed the increase of all enzymes activities in koji compared to the control inoculum (1:0).